With Fire and Sword : Arkansas, 1861-1874 - DeBlack, Thomas A., 1951- (Book collections on Project MUSE., 2003)
Thomas A. DeBlack is an associate professor of history at Arkansas Tech University. He is co-author of Arkansas: A Narrative History and the co-editor of The Southern Elite and Social Change: Essays in Honor of Willard B. Gatewood.